1975
DOI: 10.1073/pnas.72.12.5046
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regulation of immunoglobulins: kappa allotypes in the rat have multiple amino-acid differences in the constant region.

Abstract: Immunoglobulin kappa chains from various inbred strains of rats have two serologically detectable forms that segregate in a Mendelian fashion (allotypes a and b of the RI-1 locus). Partial amino-acid sequences from the constant regions of these two forms have been compared. Of the 81 residues of the constant region studied, 10 amino-acid substitutions as well as one size difference (sequence gap) were found. This large number of sequence differences among alternative forms of the K allotype raises provocative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
12
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Amino Acid Sequence ofRI-lb CK The amino acid sequence of the RI-lb protein deduced from the nucleotide sequence is consistent with the published amino acid sequences ofLOU and LEW K chains (21)(22)(23), with the exception of the arginine at amino acid position 155 (nucleotides 618-620). Our sequence is Glu-Arg-Arg-Asp at this point, where the previous studies A 2 1 indicated Glu-Arg-Asp.…”
supporting
confidence: 48%
See 4 more Smart Citations
“…Amino Acid Sequence ofRI-lb CK The amino acid sequence of the RI-lb protein deduced from the nucleotide sequence is consistent with the published amino acid sequences ofLOU and LEW K chains (21)(22)(23), with the exception of the arginine at amino acid position 155 (nucleotides 618-620). Our sequence is Glu-Arg-Arg-Asp at this point, where the previous studies A 2 1 indicated Glu-Arg-Asp.…”
supporting
confidence: 48%
“…The high degree of conservation of the three-dimensional structure of Ig domains (31) indicates that many random changes must be "forbidden." In addition, as has been pointed out previously (21), the spatial distribution of amino acid substitutions between the two RIP-alleles is highly nonrandom.…”
mentioning
confidence: 69%
See 3 more Smart Citations